Control of Alcoholic Drinks Distribution in Supporting Tourism Business - Fitria Ramadhani Nuraini (Newinera Publisher, 2020)
In Surabaya city, the demand for alcoholic drinks by tourists is quite high so that sales of alcoholic drinks support the running of tourism businesses such as hotels, bars, restaurants, pubs, night clubs and discotheques. The purpose of this article is to find out how to control the sales of alcoholic drinks in supporting the tourism business in Surabaya City and law enforcement efforts in controlling the distribution and sale of alcoholic drinks in the tourism business. The method used in this article is statute approach and conceptual approach. The results is related to this case, the government is making efforts to supervise and control the distribution of alcoholic drinks by making laws and regulations related to the control of the distribution of alcoholic drinks and stipulating requirements for tourism places that sell alcoholic drinks, one of which must have special permits. Administrative law enforcement consists of preventive administrative law enforcement, namely in the form of supervision and repressive administrative law enforcement, in the form of the application of administrative sanctions.